2003
DOI: 10.1034/j.1399-3011.2003.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the aggregation and possible channel formation in membranes of a cyclic hexapeptide, cyclo (d‐Ala‐l‐Pro‐l‐Ala)2

Abstract: The interaction of zwitterionic lipid DMPC and DPPC with cyclic hexapeptide, cyclo (D-Ala-L-Pro-L-Ala)2 was studied using circular dichroism (CD) and differential scanning calorimetry (DSC). Preliminary membrane conductance results showed that the peptide has a tendency to form channels inside the lipid bilayer. CD studies indicated that as the lipid/peptide (L/P) ratio (DMPC/peptide) was increased, the magnitude of the negative CD band having a lambda(max) around 200 nm decreased. At a L/P ratio of 210:1, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…who observed electron (and optical) microscopy images of unconjugated CPs in bundles (microcrystals) . We interpret the SANS patterns to mean that CP1 exists as bundles of short tubes in [D 6 ]DMSO, a concept that has also been proposed in the study of CP ion channel mechanism . Indeed, although early work in the field presented the mechanism of ion transport through the internal cavities of cyclic peptide nanotubes, assembly into ‘barrel and stave’ structures has also been suggested .…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…who observed electron (and optical) microscopy images of unconjugated CPs in bundles (microcrystals) . We interpret the SANS patterns to mean that CP1 exists as bundles of short tubes in [D 6 ]DMSO, a concept that has also been proposed in the study of CP ion channel mechanism . Indeed, although early work in the field presented the mechanism of ion transport through the internal cavities of cyclic peptide nanotubes, assembly into ‘barrel and stave’ structures has also been suggested .…”
Section: Resultsmentioning
confidence: 74%
“…and Kodama et al. have shown that the transport of ions is possible with cyclic peptides with only 4 or 6 residues, for which the internal pore is too small to allow ion transport, thus suggesting a barrel and stave assembly …”
Section: Resultsmentioning
confidence: 99%